IMPLIKASI PEMIKIRAN PENDIDIKAN HUMANISTIK TERHADAP PRAKTIK PEMBELAJARAN DI ERA DIGITAL - Khairuddin Said (Universitas Muhammadiyah Mataram, 2023)
The purpose of writing this scientific article is to find out the implications of humanistic educational thinking on learning practices in the digital era. Although basically Humanistic is an approach in psychology that emphasizes the importance of understanding and respecting individuals as unique and complex creatures. But in the world of education, this approach also places great emphasis on personal development, individual growth, and a deep understanding of students as unique individuals who are developed through learning. In the digital era where learning is more in contact with tools and media indirectly, then what are the implications of humanistic educational thinking on current learning practices, especially the effects on students.